2014
DOI: 10.1021/la5029806
|View full text |Cite
|
Sign up to set email alerts
|

Switching at the Nanoscale: Light- and STM-Tip-Induced Switch of a Thiolated Diarylethene Self-Assembly on Au(111)

Abstract: The light-induced and STM-tip-induced switching of photochromic thiol functionalized terphenylthiazole-based diarylethene self-assembly on Au(111) has been investigated in ambient conditions. For such a purpose, we took advantage of the formation of highly ordered domains of opened-ring (1o) or closed-ring (1c) diarylethene isomers. We evidenced a STM-tip-induced switching for the 1o isomer characterized by a tip bias threshold of 1000 mV above which switching of all molecules of the ordered 1o domains occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Intriguingly, they found that if a single o form is embedded in a SAM of c forms, conversion of the former to the latter is induced by lower bias voltages and found to be stable. These results indicate strong environmental effects on the switching process …”
Section: Stm Of Diarylethenesmentioning
confidence: 82%
See 2 more Smart Citations
“…Intriguingly, they found that if a single o form is embedded in a SAM of c forms, conversion of the former to the latter is induced by lower bias voltages and found to be stable. These results indicate strong environmental effects on the switching process …”
Section: Stm Of Diarylethenesmentioning
confidence: 82%
“…For terarylenes, two studies on STM of SAMs of 3 (Figure a) were reported. The switching unit was a terthiazole derivative functionalized with a long alkyl chain spacer group terminated by a thiol to anchor the molecule on an Au(111) surface . In a preliminary letter, Lacaze and co‐workers deposited ethanol solutions of o forms and a mixture of o and c forms on a metallic surface.…”
Section: Stm Of Diarylethenesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be overcome by using a short, insulating alkyl chain as linker to decouple the photochromic core from the surface electrons i.e. reducing molecular π-electron interaction with surface atoms [32] . However, these alkyl groups are highly resistive thus diminishing applicability of the resulting hybrid system as molecular electronics element.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies this was overcome by adapting the linking groups to the electrode material. This efficiently separates (decouples) the MOs of the electronic system from the electrodes thus enabling at least the ring-closing reaction [2,18,32] .…”
Section: Introductionmentioning
confidence: 99%